Pengaruh Persepsi Risiko, Customer Value dan Persepsi Harga Terhadap Minat Beli Ulang Produk Fashion Heuvel Tribe di Yogyakarta - Lestari, Monica; Nuvriasari, Audita (Journal of Humanities Education Management Accounting and Transportation, 2025)
This study aims to analyse the effect of risk perception, customer value, and price perception on repurchase intention of Heuvel tribe Fashion Products. The sample in this study used 100 respondents using the non-probability sampling technique. The results of the Instrument Test state that the data in this study have proven to be valid and reliable. The results of the Classical Assumption Test stated that the data in this study were normally distributed and produced a regression model that was free from multicollinearity and heteroscedasticity. The results of this study prove that: (1) Perceived Risk has a negative and significant effect on repurchase intention for Heuvel Tribe Fashion Products. (2) Customer Value has a positive and significant effect on repurchase intention of Heuvel Tribe Fashion Products. (3) Price Perception has a positive and significant effect on repurchase intention of Heuvel Tribe Fashion Products.